Analysis of the Cost Efficiency of Using Feed with Different Types of Feed and Ducks - Gunawan, Aam; Hapsah, Audita; Sugiarti, Sugiarti; Rostini, Tintin; Samudera, Raga (Jurnal Agrosci, 2024)
This study examined how cost-effective it was to raise three distinct kinds of ducks using three different types of feed. The results of this study should help researchers and the general public, particularly breeders, by supplying information on the kinds of feed and duck varieties that are more cost-effective in duck farming. Three distinct types of feed and three distinct breeds of ducks were used in this investigation. The study used an experimental design with a factorial pattern (3 x 3) and a completely randomized design (CRD), with three replications made up of two components with the codes factor A and factor B. A1 (feed BR1), A2 (feed PP3), and A3 (feed mix) make up factor A, which is the type of feed. Duck types comprise factor B, which includes B1 (Peking duck), B2 (Mojosari duck), and B3 (MA duck). The factors that were observed were feed cost per gain (FCG), economic efficiency of ration usage (EEPP), and efficient use of rations (FE). The acquired data were subjected to variance analysis (ANOVA), and the Duncan multiple range test (DMRT) was used to determine how the treatments differed. The study indicated that variables A and B did not interact in treatments. Regarding the cost-effectiveness of using feed, factor A had a highly significant effect (P > 0.01). However, factor B had no discernible impact. This study concludes that the PP3 type of ration, which uses the more efficient Peking duck, has the best cost-efficiency when using rations. Based on the study findings, the recommendation is to employ Peking ducks fed PP3 diets to raise broiler ducks to their maximum body weight while minimizing ration expenses.